Is the rate of adverse reaction to rabies vaccine in China really as the public thinks?-based on a meta analysis - Wenmin Li; Siyu Liu; Siyang Qian; Jianghan Zhu; Jonathan Nimal Selvaraj; Xiaoyan Zhang (Taylor & Francis Group, 2021)
Objective To evaluate the rate of adverse reaction toward rabies vaccine in China from 2008 to 2019, explore its characteristics and to provide a scientific and objective basis for future policy decisions. Methods Literature on the rate of adverse reaction to rabies vaccine in China from 2008 to 2019 was retrieved and collected in CNKI, Wanfang, VIP databases, PubMed and Embase. A meta analysis was carried out then. Results Totally, 35 articles were included. The combined rate of adverse reaction to rabies vaccine was 5.6% (95% CI = 5.1% - 6.0%). Adverse reactions to rabies vaccine were 11.3% and 4.5% before and after 2011, 5.3% and 7.1% in the eastern and midwestern regions, 13.2%, 25.5% and 3.7% in the tertiary hospitals, secondary hospitals and primary medical institutions, respectively. And 13.3% were in the areas where the Changchun immortal vaccine was used. The combined rate of adverse reaction to rabies vaccine inoculated in Changsheng vaccine area was 5.1%. Conclusion After 2011, the rate of adverse reaction to rabies vaccine in China has decreased dramatically. The rate of adverse reaction to rabies vaccine in the midwestern regions is higher than the counterpart in the eastern regions. The primary medical institutions are lower than the counterpart in the tertiary and secondary hospitals.